Servant leadership practice among selected Malaysian executives attending a leadership development course - Yong, Brenda May Yeen (2013)
Servant leadership calls for leaders to lead others by being a servant first and thus brings about human capital development that contributes to the organisation’s success. The purpose of this study is to investigate servant leadership practices among selected Malaysian executives attending a leadership development course. Its primary aim is to determine the level of servant leadership practices and the relationship between emotional intelligence, motivation, integrity, spirituality, mentoring and servant leadership practices. Servant leadership practices in this study comprise the five servant leadership factors of altruism, emotional healing, wisdom,persuasive mapping and organisational stewardship. The study also examines the moderating effects of gender and organisational commitment on servant leadership practices. The systematic random sampling survey approach was used to gather data from 480 executives who attended a leadership training course. Six measuring instruments were adapted to obtain the various measures including the Servant Leadership Questionnaire (SLQ) and a survey questionnaire was designed to include the measuring instruments and collect demographic background information about the participants’ age, gender and working experience. The research findings reveal that the level of servant leadership practices is moderately high (M = 3.04, SD = .33). In addition, males (M = 3.04, SD = .33) and females (M = 3.05, SD = .33) are not significantly different in their servant leadership practices. Not surprisingly, high organisational commitment executives (M = 3.11, SD = .31) show distinctly higher servant leadership practices compared to the low organisational commitment executives (M = 2.95, SD = .31). The results of the study indicate that the three independent variables of mentoring (r = .53, p = .0001), spirituality (r =.51, p = .0001) and emotional intelligence (r = .42, p = .0001) have a strong and positive relationship with servant leadership practices. In addition,spirituality (SE B = .342) is the best predictor for servant leadership practices,followed by mentoring (SE B = .295), and emotional intelligence (SE B =.170). Results of the moderated multiple regression reveal that gender is not a moderator for the relationship between emotional intelligence, motivation,integrity, spirituality, mentoring and servant leadership practices. The findings also show that organisational commitment is a moderator only for the relationship between spirituality and servant leadership practices. Finally, it must be pointed out that this is one of the few research studies on servant leadership practices in Malaysia. No national norms are available to aid in understanding the level of servant leadership practices in Malaysia. More studies in Malaysia replicated over samples covering a wide range of age groups and geographical areas in Malaysia would help to enhance the understanding of the levels of servant leadership practices in Malaysia.